2009
DOI: 10.1111/j.1365-2788.2009.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perceived stigmatisation on the quality of life among ageing female family carers: a comparison of carers of adults with intellectual disability and carers of adults with mental illness

Abstract: This study suggests that attempts to improve these female older family carers' health and social support must include their lifelong unmet needs in terms of how to cope with the perceived stigma associated with their position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 26 publications
5
48
2
Order By: Relevance
“…1 Having a child with the unexpected diagnosis was reported as emotionally overwhelming and stressful for some families. 1 Having a child with the unexpected diagnosis was reported as emotionally overwhelming and stressful for some families.…”
Section: Introductionmentioning
confidence: 99%
“…1 Having a child with the unexpected diagnosis was reported as emotionally overwhelming and stressful for some families. 1 Having a child with the unexpected diagnosis was reported as emotionally overwhelming and stressful for some families.…”
Section: Introductionmentioning
confidence: 99%
“…K. Ekwall, Sivberg, & Hallberg, 2007;Ratcliffe, Lester, Couzner, & Crotty, 2013). Those with poor health, low social support, perceived stigma (Chou, Pu, Lee, Lin, & Kroger, 2009), living alone (Ratcliffe et al, 2013), feeling lonely, and with a small or nonexistent network (A. Ekwall et al, 2004) are also more likely to be affected.…”
Section: Introductionmentioning
confidence: 99%
“…This is not consistent with the findings of previous studies. On the one hand, there are studies that do not compare men and women (Robison et al 2009) and those with sample groups made up entirely of women (Chou et al 2009). Other studies found that the impact on mental health was greater in women than in men (Navaie-Waliser et al 2002;Roth et al 2007).…”
Section: Discussionmentioning
confidence: 97%